Fluorocarbon Oil Reinforced Triple Emulsion Drops. Issue 38 (1st August 2016) - Lee, Hyomin; Choi, Chang‐Hyung; Abbaspourrad, Alireza; Wesner, Chris; Caggioni, Marco; Zhu, Taotao; Nawar, Saraf; Weitz, David A.
Abstract : Fluorocarbon oil reinforced triple emulsion drops are prepared to encapsulate a broad range of polar and non‐polar cargoes in a single platform. In addition, it is demonstrated that the fluorocarbon oil within the emulsion drop acts as an effective diffusion barrier, as well as a non‐adhesive layer, enabling highly efficient encapsulation and retention of small molecules and active biomolecules in microcapsules.